Conceptual Model of Technology Acceptance Model Modification on Robo Advisor Acceptance in Indonesia - Arief Fahruri; Mohammad Hamsal; Asnan Furinto; Rano Kartono (Journal of International Conference Proceedings, 2022)
The success factor in implementing new technology is the acceptance and use of the technology by users. Indonesia is a country with significant investor growth since 2018 with the presence of technology that makes it easier to open accounts and online transactions. Is the presence of Robo advisor technology in investment products also expected to be acceptable like existing online investment applications? This paper provides a conceptual TAM model by adding UI/UX and Security as the driver of Perceived Usefulness (PU) and Perceived Ease of Use (PEU). We also add Trust and Expected Return variables related to financial variables. So that the proposed model can be used as a basis for empirical research in the future to validate the context of accepting Robo advisors in Indonesia.Â Keywords: UI & UX, Security, Trust, Expected Return, Intention to Use, Actual Use.